ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI PARTISIPASI KERJA PEREMPUAN BERSTATUS MENIKAH DI INDONESIA - Kukuh Arisetyawan; Nadya Belva Callista; Rachmawati, Lucky; Eviana Hutabarat, Ruth (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2024)
The study was conducted with the aim of analyzing the factors that are thought to influence the work participation of married women in Indonesia. Female labor participation is considered important because it can help accelerate the rate of economic growth in Indonesia. Meanwhile, the data in this research is raw data from the 2020 National Labor Force Survey (sakernas) published by the Indonesian Central Statistics Agency (BPS). The research method in this study is a quantitative method, while the data analysis method uses binary logistic regression analysis. The results showed that overall the predicted factors affecting the work participation of married women in Indonesia showed a significant influence. It was found that the education level variable showed a negative significant effect, which means it tends to decrease the probability of married women participating in the labor market, while the age, employment sector, and income variables showed a positive significant effect, which means it tends to increase the probability of married women participating in the labor market. Key Words: Female Labor Participation, Economic Growth, Gender Inequality